U-Pb age characteristics of detrital zircon and provenance analysis of a Middle Miocene submarine fan in the Qiongdongnan Basin - Shengli GONG; Zhuoyu YAN; Baiqiang LI; Tongyao ZHANG; Turong WU; Junfeng PENG; Lei ZHENG; Dongfeng ZHANG; Xiangsheng HUANG; Chengfei LUO; Ren WANG (地质科技通报)
Objective The middle Miocene submarine fan in the Qiongdongnan Basin is an important target for natural gas exploration in the northern South China Sea. However, there has been no consensus on the source of submarine fan sediments for a long time. Provenance analysis will be important for the optimization of natural gas exploration in this area. Methods In this paper, the detrital zircon U-Pb age spectrum characteristics of drilling cores from the middle Miocene submarine fan in the Qiongdongnan Basin were analysed and compared with the U-Pb ages of zircons from potential provenance areas to determine the source of submarine fans in the study area. Results The results show that ① the U-Pb ages of detrital zircons from the N-1, N-2, N-3 and N-4 wells in the northern part of the basin are characterized by Yanshanian (160, 157, 133, 107, 102, 99 Ma), Indosinian (249, 241, 239 Ma) and Caledonian (466, 455 Ma) age peaks and have high similarity with the U-Pb age characteristics of detrital zircons from Hainan Island sediments but low similarity with the U-Pb age characteristics of detrital zircons from Red River and central Vietnam sediments. ② The detrital zircon U-Pb ages of three wells (S-1, S-2, and S-3) in the southern part of the basin show peak ages of Caledonian (435, 431, 425 Ma), Hercynian (396, 392 Ma), Indosinian (242, 238, 237 Ma), and Yanshanian (143 Ma). The S-2 well has a younger unimodal Himalayan (21 Ma) age peak. Conclusion The provenance of the middle Miocene in the northern part of the basin is Hainan Island. The influence of the provenance on the Red River and Central Vietnam is very limited. The provenance of the middle Miocene in the southern Qiongdongnan Basin was a double-source supply from the Red River and Hainan Island and was dominated by the former, with an obvious difference from west to east.